Effects of novel multicomponent exercise programs on brain-derived neurotrophic factor levels and physical fitness in older women - Mayara Imaizumi; Walter Sepulveda-Loyola; Bruna Prado Gomes; Camila Pereira; Fabiana Cristina Scherer; Regina Célia Poli-Frederico; Andréa Name Colado Simão; Vanessa Suziane Probst; Denilson de Castro Teixeira (Medwave)
Introduction Multicomponent exercise programs have demonstrated benefits for both cognitive and physical function. However, their effects on brain-derived neurotrophic factor (BDNF) levels remain inconsistent, particularly in protocols incorporating functional exercises. This study aimed to evaluate the impact of two distinct multicomponent exercise protocols on BDNF levels and physical fitness in older women.